Continuity and Change in Gang Membership and Gang Embeddedness. (May 2013) - Pyrooz, David C.; Sweeten, Gary; Piquero, Alex R.
Objectives. Drawing from social network and life-course frameworks, the authors extend Hagan's concept of criminal embeddedness to embeddedness within gangs. This study explores the relationship between embeddedness in a gang, a type of deviant network, and desistance from gang membership. Method. Data were gathered over a five-year period from 226 adjudicated youth reporting gang membership at the baseline interview. An item response theory model is used to construct gang embeddedness. The authors estimate a logistic hierarchical linear model to identify whether baseline levels of gang embeddedness alter the longitudinal contours of gang membership. Results. Gang embeddedness is associated with slowing the rate of desistance from gang membership over the full five-year study period. Gang members with low levels of embeddedness leave the gang quickly, crossing a 50 percent threshold in six months after the baseline interview, whereas high levels of embeddedness delays similar reductions until about two years. Males, Hispanics, and Blacks were associated with greater continuity in gang membership as well as those with low self-control. Conclusions. The concept of gang embeddedness broadens understanding of heterogeneity in deviant network immersion and is applicable to a wide range of criminal and delinquent networks. Gang embeddedness has implications for studying the parameters of gang careers and for a range of criminological outcomes.